ETHNOSCIENCE STUDY OF THE PROCESS OF MAKING ADEM POWDER AS A SCIENCE LEARNING RESOURCE IN JUNIOR HIGH SCHOOL - Aisah, Siti; Nada, Imma Kothrun; Fawaida, Ulya; Hikmah, Saffanatul; Mua’azah, Luluk Ulfatul (Bio-Lectura : Jurnal Pendidikan Biologi, 2025)
Natural Sciences (Science) has a significant role in improving students' ability to understand various natural events around them, including in the context of junior high school science material. This study aims to explore the process of making traditional cooling powder as a source of science learning (IPA) based on ethnoscience for junior high school students. The research was conducted in Kandangmas Village, Kudus, using a qualitative descriptive method. The main source was a traditional midwife with expertise in creating cooling powder from key ingredients such as rice, turmeric, and aromatic ginger (kencur). The stages include soaking, grinding, mixing, shaping, and drying. This study links the process to science concepts, such as changes in the state of matter, frictional force, pressure, density, and heat transfer. The results indicate that integrating local wisdom with scientific concepts can enhance students’ understanding of science through cultural context. This approach also strengthens the preservation of local cultural heritage while fostering students’ love for their culture and national identity. Utilizing ethnoscience in education provides meaningful, relevant, and contextual learning experiences. Therefore, a culturally-based science learning approach can offer innovative solutions to improve student engagement and preserve local knowledge amidst globalization challenges.